Internet censorship detected in Turkey (Turkey) - Voidly (2026)
CRITICAL severity censorship detected in Turkey. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2026-0129
Keywords: censorship; TR; censorship; critical